Glacial Dispersal - Principles and Practical Applications - Shilts, W. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1982)
Abstract Glacial dispersal, the process of glacialerosion, transportation and deposition,has distorted the bedrock signatures onoverlying surficial sediments and soils inmost of Canada. Buffering components,such as carbonate minerals, which miti-gate the effects of acid rain have beendispersed across Precambrian terrane ineastern Ontario in patterns that reflectseveral principles of glacial dispersal.Dispersal trains of boulders, minerals,and trace elements may enhance the sizeof mineral exploration targets by severaltimes. By using appropriate analyticalstrategies and knowledge of dispersal,the source mineralizations can be found,as illustrated by an example of dispersalof nickel from the District of Keewatin.One other way dispersal principles havebeen applied has been to calculate thevolume of material dispersed from a par-ticular source outcrop. Dividing thatvolume by outcrop area yields averagedepth of glacial erosion, an importantparameter to consider in selecting mini-mum depths for burial of long-lived radio-active waste.